1997
DOI: 10.1103/physrevlett.79.937
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in Nanocrystalline57Fe

Abstract: We measured the phonon density of states (DOS) of nanocrystalline Fe by resonant inelastic nuclear g-ray scattering. The nanophase material shows large distortions in its phonon DOS. We attribute the high energy distortion to lifetime broadening. A damped harmonic oscillator model for the phonons provides a low quality factor, Q u , averaging about 5, but the longitudinal modes may have been broadened most. The nanocrystalline Fe also shows an enhancement in its phonon DOS at energies below 15 meV. The differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
115
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(132 citation statements)
references
References 22 publications
14
115
0
Order By: Relevance
“…Measurements on sputtered Fe films with different thickness [24] and nanocrystalline films [25] showed that an enhancement of the low energy phonon DOS correlates with increasing disorder. This enhancement of the low energy DOS would result in a lower Θ D as observed in our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements on sputtered Fe films with different thickness [24] and nanocrystalline films [25] showed that an enhancement of the low energy phonon DOS correlates with increasing disorder. This enhancement of the low energy DOS would result in a lower Θ D as observed in our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Phonon DOS has been determined for a number of iron compounds and alloys: FeO [519,520], FeS [521], Fe-Ni [522], Fe-Si alloys [287,522], FeH [523], Fe3S [524], Fe3C [525][526][527], Fe2O3 [528], (Mg,Fe)O [497], and (Mg,Fe)SiO3 enstatite [529]. For nanocrystalline Fe, large distortions were found in its phonon DOS [530], showing a lifetime broadening at high energies and an enhancement in its phonon DOS at energies below 15 meV.…”
Section: Phonon Density Of Statesmentioning
confidence: 99%
“…Enhanced intensity above the high-energy cutoff of the bulk material has been attributed to phonon lifetime broadening caused by phonon interactions with grain boundaries [9][10][11] and recent measurements on iron have isolated a contribution from surface oxides [12]. The increased number of phonon modes at low energies [5][6][7][8][9][10][11] is less well understood. The phonon density of states (DOS) at low energies is up to a factor of 5 times larger than the DOS of control samples of material composed of larger crystals [10].…”
mentioning
confidence: 98%
“…More recently, neutron and x-ray inelastic scattering measurements revealed that nanocrystalline materials have an increased number of vibrational modes at the highest and lowest energies of their measured spectra, compared to materials with crystals of conventional sizes [5][6][7][8][9][10][11][12]. Enhanced intensity above the high-energy cutoff of the bulk material has been attributed to phonon lifetime broadening caused by phonon interactions with grain boundaries [9][10][11] and recent measurements on iron have isolated a contribution from surface oxides [12]. The increased number of phonon modes at low energies [5][6][7][8][9][10][11] is less well understood.…”
mentioning
confidence: 99%